Theoretical Analysis of a pn-Diode on AIN with Distributed Polarization Doping - Faber, Samuel; Witzigmann, Bernd (physica status solidi (a), 2025)
Distributed polarization doping (DPD) represents a promising pathway toward high aluminum ((Formula presented.)) mole fraction aluminum gallium nitride ((Formula presented.)) electronic devices. In order to design more complex high (Formula presented.) mole fraction devices such as transistors, accurate device modeling is a valuable tool. This article provides a theoretical analysis including special peculiarities of DPD heterojunction devices, material parameters appropriate for high (Formula presented.) mole fraction (Formula presented.) materials, and geometry, e.g., rotational symmetry. Moreover, the article studies the temperature-dependent mobility of DPD devices and addresses the breakdown capabilities of high (Formula presented.) mole fraction (Formula presented.) materials.
CRIS-Team Scopus Importer:2025-12-05
Keywords: AlGaN; AlN; distributed polarization doping; heterojunction; pn-diode; polarization-induced doping